TINJAUAN INFORMASI AKUNTANSI MANAJEMEN LABA TERHADAP REAKSI PASAR DENGAN MODEL JONES MODIFIKASIAN DI SEKTOR PERDAGANGAN, JASA, DAN INVESTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Noer Ainy Rimadhany; Pujiono (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This study aims to investigate the earnings management practices of trading, service, and investment companies on the Indonesia Stock Exchange (IDX) on stock prices after IFRS adoption in Indonesia. Using a quantitative methodology, data was collected through purposive sampling of the annual financial reports of the relevant companies from 2015-2020. Earnings management, assessed using the modified Jones model, and stock price, determined on the closing date, are the focal variables of the study. This study uses linear regression analysis with panel data. The findings of this study indicate a significant correlation between earnings management and stock price, indicating that the practice has an impact on the investment decisions of companies in the trading, services, and investment sectors listed on the Indonesia Stock Exchange.